Tissue-resident immune cells: from defining characteristics to roles in diseases - Jia Li; Chu Xiao; Chunxiang Li; Jie He (Signal Transduction and Targeted Therapy)
Abstract Tissue-resident immune cells (TRICs) are a highly heterogeneous and plastic subpopulation of immune cells that reside in lymphoid or peripheral tissues without recirculation. These cells are endowed with notably distinct capabilities, setting them apart from their circulating leukocyte counterparts. Many studies demonstrate their complex roles in both health and disease, involving the regulation of homeostasis, protection, and destruction. The advancement of tissue-resolution technologies, such as single-cell sequencing and spatiotemporal omics, provides deeper insights into the cell morphology, characteristic markers, and dynamic transcriptional profiles of TRICs. Currently, the reported TRIC population includes tissue-resident T cells, tissue-resident memory B (BRM) cells, tissue-resident innate lymphocytes, tissue-resident macrophages, tissue-resident neutrophils (TRNs), and tissue-resident mast cells, but unignorably the existence of TRNs is controversial. Previous studies focus on one of them in specific tissues or diseases, however, the origins, developmental trajectories, and intercellular cross-talks of every TRIC type are not fully summarized. In addition, a systemic overview of TRICs in disease progression and the development of parallel therapeutic strategies is lacking. Here, we describe the development and function characteristics of all TRIC types and their major roles in health and diseases. We shed light on how to harness TRICs to offer new therapeutic targets and present burning questions in this field.